Plant responses to flooding - Rashmi Sasidharan (Frontiers Research Topics, 2015)
Global warming has dramatically increased the frequency and severity of flooding events worldwide. As a result, many man-made and natural ecosystems have become flood-prone. For plants, the main consequence of flooding is the drastic reduction of oxygen availability that restricts respiratory energy production and finally affects survival. Flooding can negatively influence crop production and wild plant distributions, since most plants are sensitive to excessively wet conditions. However, plants have evolved a broad spectrum of adaptive responses to oxygen deficiency that eventually leads to tolerance. Many of these morphological and physiological adaptations have been described in some crops and wild plant species and considerable progress has been made in understanding the molecular aspects governing tolerance traits. Moreover, the molecular mechanism of plant oxygen sensing has been recently elucidated. However, many other aspects concerning plant acclimation responses to flooding remain unanswered. With this research topic we seek to build an online collection of articles addressing various aspects relating to "plant responses to flooding'' which will reflect the exciting new developments and current state of the art in this vibrant and dynamic research field. All kinds of articles, including original research articles, short reviews, methods and opinions are welcome, in the attempt to broadly and freely disseminate research information, tools and protocols.